Proverbial expressions in newspapers – A comparative study in Estonia, Finland and Slovenia. - Granbom-Herranen Liisa; Babič Saša; Voolaid Piret (Zalozba Z R C,Scientific Research Centre Publishing, 2022)
This article 1 examines proverbs and proverbial expressions
in contemporary newspaper contexts and in everyday use in
three languages: Estonian, Finnish, and Slovenian. Print
editions of the Estonian newspapers Postimees and Tartu
Postimees, the Finnish newspapers Helsingin Sanomat,
Salon Seudun Sanomat, and Perniönseudun Lehti, and
the Slovenian newspaper Dnevnik were scanned for use of
proverbial material during May 2013. From the reader’s
point of view, proverbs are understood to be both etic and
emic concepts. The article discusses how to recognize contemporary
proverbial units in this study in newspaper texts. The
quantitative part of the study outlines proverbial expressions
among newspaper genres and sections, and the location of
proverbial expressions within textual units. The qualitative
part of the analysis concerns distinctive national differences
(use of proverbial expressions in horoscopes in Estonia, combined
with TV programs in Finland and opinion pieces or
letters to the editor in Slovenia) and focuses on them in a
cultural context. The qualitative study highlights the most
essential concentrations of proverbs. The differences are
outlined in the sections focusing on country-specific features.